2016
DOI: 10.1371/journal.pone.0165793
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Peptide ELISA for the Diagnosis of Aleutian Mink Disease

Abstract: Aleutian disease (AD) is a common immunosuppressive disease in mink farms world-wide. Since the 1980s, counterimmunoelectrophoresis (CIEP) has been the main detection method for infection with the Aleutian Mink Disease Virus (AMDV). In this study, six peptides derived from the AMDV structural protein VP2 were designed, synthesized, and used as ELISA antigens to detect anti-AMDV antibodies in the sera of infected minks. Serum samples were collected from 764 minks in farms from five different provinces, and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Previous studies have identified the capsid protein VP2 of FPV as a coating antigen for ELISA in the detection of antibodies against feline panleukopenia in cats [12]. In addition, the VP2 subunit protein exhibited good antigenicity in ELISA development for the detection of antibodies against parvovirus in minks causing Aleutian Mink disease with high sensitivity and specificity [20]. On that basis, the amino acids 545-585 of VP2, which covered the epitope region and were specific to the FPV, were selected and employed as an antigen in an indirect ELISA test in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified the capsid protein VP2 of FPV as a coating antigen for ELISA in the detection of antibodies against feline panleukopenia in cats [12]. In addition, the VP2 subunit protein exhibited good antigenicity in ELISA development for the detection of antibodies against parvovirus in minks causing Aleutian Mink disease with high sensitivity and specificity [20]. On that basis, the amino acids 545-585 of VP2, which covered the epitope region and were specific to the FPV, were selected and employed as an antigen in an indirect ELISA test in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, this approach has been shown to be successful in reducing the prevalence of infected mink in Nova Scotia Canada, but has failed in eradicating AMDV from most of the infected farms [ 57 ]. Despite its advantages, CIEP is not a very sensitive diagnostic technique, can yield false negative results and is very time consuming [ 58 , 59 ]. In contrast, the enzyme-linked immunosorbent assay (ELISA) is another approach that is frequently used, which is based on detecting anti-AMDV antibodies in blood with the advantage of being automated and more sensitive [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…One way to solve cross‐reactivity problems in diagnostics is to identify immunogenic epitopes exclusive to a specific pathogen . In previous studies, peptides corresponding to identified epitopes of antigenic markers of infections have been used in diagnostics …”
Section: Introductionmentioning
confidence: 99%